Produção da irregularidade urbana : gestão, agentes, processos e práticas espaciais no território de Cascavel/PR - Soares, Karen Alessandra Solek (2016)
This research addresses the issue of the management of urban irregularity in two spatial practices: irregular / illegal settlements / slums formed by areas in reparcelling approved allotments; and the irregular settlements in plots not previously splitted. The Focus is on the theme of the irregularities management is intending, as a general goal, highlight the shortcomings in technical networks of urban infrastructure within these informal spaces, produced from public or private promotion in cities of the expansion of capital. According to the legal framework and the first case, the non-compliance with some regulation, whether at the municipal, state or federal level, entails the legal irregularity of the settlement or settlement, and; consequently, to a willful neglect the provision of basic infrastructure, due to its formal absence, denying the residents of these areas the right to the city. The second hypothesis, complementing the first, suggests that the reproduction of space in meeting the infrastructure of settlements with residential purposes, it is preferred the space where there is flexibility for the realization of the financial capital. In solving the problem of research on urban needs arising from public and private actors action, we use a methodological approach to quantitative and qualitative through correlational research, based on case study, with data collection in primary and secondary sources , relating to implementation of irregular ventures with the extension of the technical infrastructure network. The city chosen for the study is Cascavel, located in the state of West meso of Paraná, evidenced in recent years, in the media and in national journals, as a city in economic and population growth, with financial investment possibilities. The theoretical framework for the study presents the Francisco de Oliveira discussions (2013) with economic policy analysis on Brazil from the 1930s, which shows the influences of national and regional planning in the consolidation of medium-sized cities in the Brazilian industrialization process. After the 1990s, the breakdown of these conceptions, point to emergency management, which fits the irregularity and its relation to the installed infrastructure. As a result of the negligence of indices or service to network infrastructure from a discussion between exchange value and use, comes the dependence of flexibility for capital market entry in these areas, even informally and without effective relationship with the property of its residents. The contribution of this study is to reflect on the management of urban irregularity present in housing developments and low-income settlements, to identify: agents, processes and spatial practices.